Textual and language features of students’ written Discussion texts - Ting, Su Hie; Chai, Ai Sze (Issues in Language Studies, 2013)
The study examined textual and language features of discussion texts written by university students. The discussion texts were written by 100 students enrolled in an English for Academic Purposes course at a Malaysian university. The advantages-disadvantages essay was analysed using Feez’s (1998) framework for discussion texts. The results showed that about half of the students were unable to state the issue clearly in the introduction and assess the issue based on foregoing arguments in the conclusion. For the arguments, the topic sentences and supporting details were satisfactory. Analysis of the language features in the student discussion texts revealed that conditional clauses were seldom used to present hypothetical situations to move the arguments forward but connectors were frequently used, particularly “because”. More causal connectors were used than sequential connectors because of the need for reasoning in discussion texts. Shifts in arguments were signaled using adversative connectors but these were used less frequently than additive connectors for connecting similar ideas. The discussion texts were also characterised by the frequent use of modal verbs for hedging and boosting, mainly “can” and “will”. The study shows that while the student texts had the relevant language features of discussions, they sometimes lacked the characteristic textual structure of discussion texts.